Chapter User-Centered Design - Doroftei, Daniela; Gancet, Jeremi; Serrano, Daniel; Cubber, Geert De; Wagemans, Rene; Matos, Anibal; Silva, Eduardo; Lobo, Victor; Cardoso, Guerreiro; Chintamani, Keshav; Govindaraj, Shashank (InTechOpen, 2021)
The successful introduction and acceptance of novel technological tools are only possible if end users are completely integrated in the design process. However, obtaining such integration of end users is not obvious, as end‐user organizations often do not consider research toward new technological aids as their core business and are therefore reluctant to engage in these kinds of activities. This chapter explains how this problem was tackled in the ICARUS project, by carefully identifying and approaching the targeted user communities and by compiling user requirements. Resulting from these user requirements, system requirements and a system architecture for the ICARUS system were deduced. An important aspect of the user‐centered design approach is that it is an iterative methodology, based on multiple intermediate operational validations by end users of the developed tools, leading to a final validation according to user‐scripted validation scenarios.